Structural and functional assessment of ganglion cell complex in patients on long-term hydroxychloroquine - Shreyas Temkar; Aniket Tatyasaheb Mairal; Arun Sahi; Amit Kumar Deb; Chengappa G Kavadichanda; Subashini Kaliaperumal; Veeradasari Jawahar Satya Babu; Aarthy Gunasekaran (Indian Journal of Ophthalmology)
Purpose: Long-term hydroxychloroquine (HCQ) treatment has been shown to be associated with structural changes (reduced thickness) of ganglion cell complex (GCC). This study evaluated if these structural changes of GCC translate to functional deficits and if they represent true retinal toxicity. Methods: This was a cross-sectional study. Fifteen patients aged ≥18 years who had been on HCQ treatment for >5 years were recruited as cases, and 15 age- and gender-matched healthy individuals were recruited as controls. All cases underwent visual fields (central 10-2 SITA standard), pattern electroretinogram (ERG), spectral-domain optical coherence tomography (OCT), and widefield autofluorescence. Controls underwent pattern ERG and spectral-domain OCT. Results: A significantly lower average (77.0 ± 5.5 µm vs. 82.0 ± 5.3 µm, P = 0.017) and minimum ganglion cell-inner plexiform layer (GC-IPL) thickness (71.0 ± 8.1 µm vs. 76.6 ± 6.3 µm, P = 0.041) were noted among cases compared to controls. Similarly, average retinal nerve fiber layer (RNFL) thickness (86.7 ± 9.6 µm vs. 94.8 ± 7.6 µm, P = 0.015) and superior quadrant RNFL thickness (105.2 µm ± 16.7 µm vs. 120.0 µm ± 15.6 µm, P = 0.018) were lower in cases than in controls. Average RNFL thickness and GC-IPL thickness were negatively correlated with the mean deviation (MD), the pattern standard deviation (PSD) scores, and implicit times of P50 and N95 waveforms, respectively, but none were statistically significant. Conclusion: Long-term HCQ use is associated with structural changes in the GCC, manifested as lower GC-IPL and RNFL thickness. Although there was a trend suggesting ganglion cell dysfunction (prolonged implicit times) and possible deficits in RNFL function (MD and PSD scores), statistically significant correlations could not be established with GC-IPL and RNFL thickness, respectively. GC-IPL/RNFL thickness assessment can be a part of the screening. Mere GC-IPL thickness reduction should not be a criterion to recommend HCQ cessation in the absence of abnormality on routinely recommended screening tests.